KINERJA ANGGOTA SATUAN PERLINDUNGAN MASYARAKAT DALAM MENCIPTAKAN KEAMANAN, KETENTRAMAN DAN KETERTIBAN DI KECAMATAN MALINAU KOTA KABUPATEN MALINAU - Daniel Anyik (Jurnal Administrative Reform, 2020)
The purpose of this study is to describe and analyze the performance of the Community Protection Unit Officers in creating Security, Peace, and Order in Kecamatan Malinau Kota, Malinau District. This type of research includes descriptive with a qualitative approach. Primary data is derived from interviews with informant selected purposively and direct observation, supported by secondary data derived from written data owned by the agency. The conclusion of the research was conducted through interactive model data analysis. The results showed that the work of Satlinmas members in creating security, peace, and order in Kecamatan Malinau Kota as measured by several performance instruments, including the ability to finish the task, the quality of the work, the attitude of work discipline, creativity in working, and cooperation with the community showed good work results, but not optimal.Keywords: Performance, Community Protection, Security, Peace, Order